2022
DOI: 10.3389/fnut.2022.833906
|View full text |Cite|
|
Sign up to set email alerts
|

Fermentation and Storage Characteristics of “Fuji” Apple Juice Using Lactobacillus acidophilus, Lactobacillus casei and Lactobacillus plantarum: Microbial Growth, Metabolism of Bioactives and in vitro Bioactivities

Abstract: Fruit juices have been widely used as the substrates for probiotic delivery in non-dairy products. In this study, three lactic acid bacteria (LAB) strains, including Lactobacillus acidophilus, Lactobacillus casei and Lactobacillus plantarum, were selected to ferment apple juice. During 72-h of fermentation, these LAB strains grew well in the apple juice with significant increases in viable cell counts (from 7.5 log CFU/mL to 8.3 log CFU/mL) and lactic acid content (from 0 to 4.2 g/L), and a reduction of pH val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 64 publications
5
21
0
Order By: Relevance
“…Pyruvate is an intermediate product in the organism’s metabolic pathways, such as the tricarboxylic acid cycle and glycolysis. Pyruvate can be produced from glucose via the glycolytic pathway but can also be converted to lactic acid via the lactic acid fermentation pathway ( 42 ). Therefore, its content may show a dynamic equilibrium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyruvate is an intermediate product in the organism’s metabolic pathways, such as the tricarboxylic acid cycle and glycolysis. Pyruvate can be produced from glucose via the glycolytic pathway but can also be converted to lactic acid via the lactic acid fermentation pathway ( 42 ). Therefore, its content may show a dynamic equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…The total phenolic content in apple juice decreased from 331.43 ± 3.38 to 286.52 ± 3.15 ( p < 0.05) and 258.25 ± 5.66 mg GAE/L ( p < 0.05) after fermentation by WFC 414 and WFC 502, respectively. This may be due to Lactobacillus synthesizes decarboxylase, tannase, and glycosidase during fermentation to enhance the decomposition and metabolic conversion of polyphenols ( 42 ). Gallic acid can improve the antioxidant properties of FAJ, and its significant increase may come from the hydrolysis of tannins in the juice.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent study observed that fermentation of apple juice with three probiotic strains, i.e., Lactobacillus acidophilus, Lactobacillus casei, and Lactobacillus plantarum significantly increased its antioxidant capacity as determined by ABTS radical cation scavenging capacity and ferric reducing ability of plasma (FRAP) as well as antibacterial potency against common microbial food contaminants Escherichia coli and Staphylococcus aureus through improved phenolic and organic acid metabolism (Yang et al 2022). Fermentation of apple juice with Lactobacillus plantarum improved the total flavonoid content and DPPH radical scavenging capacity (up to 36.08%) which were also accompanied by the production of new volatile compounds such as propanol, citronellol, ethyl lactate and hexyl butyrate .…”
Section: Fermented Fruits and Vegetablesmentioning
confidence: 99%
“…Apples and tomatoes have high nutritional quality, and various studies have shown that their juices are suitable raw materials for fermented beverages [22][23][24]. Apples contain carbohydrates, polyphenols, organic acids, vitamins, and minerals [25].…”
Section: Introductionmentioning
confidence: 99%